Pengembangan Komik Matematika Digital pada Materi Aritmetika Sosial Kelas VII SMP - Feby Attina Sari; Sripatmi Sripatmi; Baidowi Baidowi; Amrullah Amrullah (Griya Journal of Mathematics Education and Application, 2022)
This research was a development research which was aimed to producing a new product in the form of digital mathematical comic. Digital mathematical comic developed through four stages according to the 4D model procedure which are define, design, develop, and disseminate. The instrument in this study was a questionnaire used to assess the feasibility of comics and student responses. The feasibility of comics was assessed by 2 lecturers as media experts and 2 teachers as material experts. The media expert’s give an average score of 70.50 out of a total average of 80.00 with very feasible category and the material expert’s give an average score of 48.00 out of a total average of 52.00 with very feasible category. Subsequently, a trial was conducted on 26 seventh grade students at SMPN 8 Mataram. According to the student response questionnaire an average score of 14.27 was obtained from a total average of 15.00 with very feasible category. So it can be concluded that digital mathematical comics are declared very feasible for use in math learning in the classroom.